Suspended sediment load prediction using long short-term memory neural network - AlDahoul N.; Essam Y.; Kumar P.; Ahmed A.N.; Sherif M.; Sefelnasr A.; Elshafie A. (Nature Research, 2023)
article; Johor; linear regression analysis; long short term memory network; multilayer perceptron; particle resuspension; prediction; river